Effect of sharing health messages on antenatal care behavior among women involved in microfinance-based self-help groups in Bihar India - Walia, Monika (Glob Health Res Policy, 2020)
BACKGROUND: Bihar state in India has one of the highest rates of maternal and infant mortality in South Asia. Microfinance-based self-help groups (SHGs), involving rural women, are being utilized to improve maternal and child health practice and reduce mortality. SHG members receive information on key maternal and child health practices as well as encouragement for their practice. This study measures the association of health messaging to SHG members with their antenatal care (ANC) behaviors. METHODS: The study was conducted in eight districts of Bihar in 2016. A three-stage cluster sampling design (with a random selection of blocks, villages, and SHGs) selected the sample of 1204 SHG members who had an infant child; of these, 597 women were members of SHGs that received dedicated sessions on health messages, while 607 women belonged to SHGs that did not. To examine the impact of the health intervention on ANC practice, radius caliper method of propensity score matching controlled for various socio-demographic characteristics between the two groups. RESULTS: Most of the interviewed women (91.5%) belonged to a scheduled caste or tribe. Nearly 44% of SHG members exposed to the health intervention were engaged in some occupation, compared to 35% of those not exposed to the intervention. After matching unexposed SHG women with exposed SHG women, no significant differences were found in their socio-demographic characteristics. Findings suggest that exposure to a health intervention is associated with increased likelihood of at least four ANC visits by SHG women (ATE = 7.2, 95% CI: 0.76–13.7, p < 0.05), consumption of iron-folic acid for at least 100 days (ATE = 8.7, 95% CI: 5.0–12.5, p < 0.001) and complete ANC (ATE = 3.6, 95% CI: 2.3–4.9, p < 0.001), when compared to women not exposed to the health intervention. CONCLUSIONS: The study shows that sharing health messages in microfinance-based SHGs is associated with significant increase in ANC practice. While the results suggest the potential of microfinance-based SHGs for improved maternal health services, the approach’s sustainability needs to be further examined.